Media effects on pro-environmental behavioral intention : an examination of illusion in perceived knowledge differential between self and others - Yang, Xiaodong (2017)
Concerning the severe effects caused by climate change to both the natural and social systems, the mitigation and adaptation to climate change is becoming an urgent public agenda. As the information source for public agenda, media are recognized as being useful in informing public about climate change. Guided by information deficit model, many communication campaigns on climate change mitigation focus on cultivating public understanding of climate change. This model postulates that people will perform behavioral change once they are informed about the issue. Accordingly, a number of communication studies focus on how attention to media messages affects individuals’ behaviors through raising their levels of actual knowledge. However, the original information deficit model has been criticized for being oversimplified. Information provision does not only affect individuals’ actual knowledge level, but also influences how people evaluate their own knowledge level. People tend to develop illusion in their evaluation of knowledge level and to act upon the illusion of knowledge. Recognizing the flaws of the original information deficit model, this study extends this model by including illusion of knowledge as an important factor that shapes behavioral change in addition to actual knowledge. Regarding illusion of knowledge, both illusion in self-evaluation of knowledge and illusion in perceived knowledge differential between self and others are taken into accounts. Accordingly, this study examined how individuals’ attention to media messages about climate change influences their actual knowledge and illusion of knowledge of climate change, which alters their attitude toward pro-environmental behaviors, and in turn translates into behavioral intention. For data collection, this research conducted a door-to-door survey in Singapore (N = 705). The analyses of demographic differences revealed that people from different social groups have different levels of actual knowledge, illusion in self-evaluation of knowledge, and illusion in perceived knowledge differential between self and others. In line with the criticism over the original model for its over-emphasis of the simple linear process, the results from this study suggested that the extended model performed better in predicting behavioral change compared to the original model. Moreover, the results showed that individuals’ attention to media messages about climate change affect both actual knowledge and illusion of knowledge, which promote their positive attitude toward pro-environmental behaviors, and in turn motivate pro-environmental behavioral intention. In particular, the findings suggested that the more positive illusion people have in self-evaluation of knowledge and in perceived knowledge differential between self and others, the more positive attitude they would develop toward pro-environmental behaviors, which in turn increase their intention of performing the behaviors. Implications of the findings, limitations of the study and directions for future research were also discussed.